Tinjauan Yuridis Realisasi Pelaksanaan Ganti Rugi Pengadaan Jalan Tol Solo-Kertosono Di Wilayah Sawahan Kabupaten Boyolali - Priyambada, Dheniswara Bryan, Shallman Al Farizi, S.H., M.Kn (2016)
This study aims to determine the development of toll road development and implementation Solo-Kertosono compensation from the government to local residents affected by the construction of toll roads in the region Solo-Kertosono Sawahan Boyolali. The method used is a normative juridical research specifications are fenomologi transcendental, because it tried to examine a phenomenon of the exclusion of prejudice. The data source consists of primary data, interviews and secondary data, legal data primary, secondary and tertiary. Data were collected by literature study and field study that observation, interviews and documentation. Furthermore, the data were analyzed qualitatively. The results showed that the development of highway construction Solo-Kertosono based on planning, location determination, the implementation of land acquisition and compensation, waiver, management of land rights, the implementation of physical development, and results of appraisal work as expected. The implementation of land acquisition for public purposes are in accordance with Law No. 2 of 2012 on Land Procurement for Public Interest among others in case of a dispute by conducting the mediation and if the parties do not agree to mediation, it can be appealed to the District Court.